Kidney transplants from elderly donors: the experience of a reference center in Croatia - Živčić-Ćosić, Stela; Süsal, Caner; Döhler, Bernd; Katalini, Natasa; Marki, Dean; Orli, Lidija; Racki, Sanjin; Spanjol, Josip; Trobonjaca, Zlatko (Experimental and clinical transplantation, 2022)
Objectives: Our country Croatia is among the global leaders regarding deceased donation rates, yet we are facing organ shortage and concurrently a sharp decline in our acceptance rates for kidney offers. To reevaluate our organ acceptance policy, we retrospectively analyzed the factors that influenced the posttransplant outcomes of kidneys from elderly deceased donors at our center during a 20-year period and the changes to our organ acceptance criteria during Eurotransplant membership. Materials and Methods: We studied all kidney transplants from donors >= 60 years old during the two 5-year episodes of Eurotransplant membership from 2007 to 2017 (period II and period III) and compared those data to data from the decade before Eurotransplant membership (period I, 1997-2007). Differences in acceptance rates and reasons for the decline of kidney offers between the two 5-year periods of Eurotransplant membership were analyzed. Results: In period I, 14.1% of all kidney allografts were obtained from donors >= 60 years old; in period II and period III the rates were nearly 2-fold higher (27.0% and 25.7%, respectively; P= .007 and P= .008). During the first 5-year period of Eurotransplant membership (period II), we accepted significantly more grafts from marginal donors with a higher number of human leukocyte antigen mismatches compared with period I. Consequently, the 3-month survival rate of kidneys from donors >= 60 years old dropped from 91.1% to as low as 74.2% (P = .034). After application of morestringent human leukocyte antigen matching, especially in human leukocyte antigen DR, and morestringent donor acceptance criteria in period III, graft survival improved to 91.1%. Conclusions: Our experience indicates that careful selection of kidneys from elderly deceased donors and allocation to human leukocyte antigen-matched recipients is important to improve transplant outcomes.
Gesehen am 13.09.2022